Rest activity rhythms characteristics of breast cancer women following endocrine therapy. Issue 4 (8th October 2021) - Martin, Tristan; Duivon, Mylène; Bessot, Nicolas; Grellard, Jean-Michel; Emile, George; Polvent, Sébastien; Raoul, Lucie; Viader, Fausto; Eustache, Francis; Joly, Florence; Giffard, Bénédicte; Perrier, Joy
Abstract: Rest-activity rhythm (RAR) disruptions are frequently associated with chemotherapy in breast cancer (BC), but they are less known in BC with endocrine therapy (ET). The aim of this ancillary study was to characterize the RAR and estimated sleep characteristics from actigraphy in BC patients either treated (ET+) or untreated with ET (ET−), compared to healthy controls (HC) and using a cross-sectional design. Eighteen ET+, 18 ET−, and 16 HC completed questionnaires and wore wrist actigraphs at home for 2 weeks. Parametric and nonparametric RAR, sleep parameters, and quality of life were compared between groups ( p < .05). BC groups presented lower daytime activity than HC according to RAR analysis (mesor and M10 parameters). Compared to HC, ET− had lower inter-daily stability and ET+ had greater sleep complaints. Compared to ET−, ET+ had lower sleep efficiency, more time awake, and higher activity levels at night, as assessed with actigraphy. Our results suggest an effect of cancer independent of treatment on RAR in BC, highlighting the need for further investigation of this topic. In contrast, sleep as assessed with actigraphy seems modified only during ET which matches with patients' sleep complaints. Further longitudinal studies would aid in confirming the latter hypothesis.